2018
DOI: 10.3168/jds.2017-13361
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Occurrence of methicillin-resistant Staphylococcus aureus and coagulase-negative staphylococci in dairy goat herds in Ohio, United States

Abstract: In light of the scarcity of information about the occurrence and epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative staphylococci (MRCNS) in small ruminants in general, and particularly dairy goats, we launched this limited-scope study. The findings reported here show the detection of MRSA and MRCNS in goat milk and teat skin samples from dairy goat herds in the state of Ohio. A total of 120 milk samples and 120 teat-swab samples were collected from 5 farms. After convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…urealyticum). These results are similar to those obtained by Moura et al (2018), who reported a frequency of 1.25% for the mecA gene in CoNS isolated from goat mastitis. Contrarily, Cantekin et al (2019), Nobrega et al (2018, Bhargava & Zang (2012), and Klimiene et al (2016) found rates of 6.6, 17, 60, and 67.8% in CoNS isolated from different animal origins.…”
Section: Resultssupporting
confidence: 92%
“…urealyticum). These results are similar to those obtained by Moura et al (2018), who reported a frequency of 1.25% for the mecA gene in CoNS isolated from goat mastitis. Contrarily, Cantekin et al (2019), Nobrega et al (2018, Bhargava & Zang (2012), and Klimiene et al (2016) found rates of 6.6, 17, 60, and 67.8% in CoNS isolated from different animal origins.…”
Section: Resultssupporting
confidence: 92%
“…In two studies from Italy, the bulk milk prevalence was 0.6 and 2%, respectively [20,21]. On an individual goat level, the MRSA prevalence has been described to range from 2% in the US and Saudi Arabia to 8% in Austria, 16% in Tenerife, Spain, and 23% in Nigeria [2,[22][23][24][25]. However, a direct comparison of the occurrence between studies should be done with care since different methods for sampling and detection are used in different studies.…”
Section: Resultsmentioning
confidence: 99%
“…-Detection of Staphylococcus sp. [31][32][33]: 1 mL of milk samples was enriched in 9 mL of Mueller-Hinton broth supplemented with 6.5% NaCl (Oxoid Ltd., Basingstoke, UK). Incubation at 37 • C for 20 h followed and 1 mL was enriched in 9 mL of Tryptone Soya broth with 10% NaCl and 1% sodium pyruvate (HiMedia Labs, Einhausen, Germany).…”
Section: Microbiological Analysesmentioning
confidence: 99%